Emergency care nurses' perceived self‐competence in palliative care and its predictors: A cross‐sectional study. (5th April 2022) - Feng, Mei; Liu, Qian; Hao, Jie; Luo, Dan; Yang, Bing Xiang; Yu, Sihong; Chen, Jie
Abstract: Aim: The aim of this study is to describe the prevalence of perceived self‐competence in palliative care among emergency care nurses and explore its predictors. Background: Emergency care nurses have a responsibility to develop palliative care competence to enhance the quality of life of dying patients and their families in the emergency department. Methods: With a convenience sample, a cross‐sectional study was conducted among 415 emergency care nurses from 22 hospitals in China. Descriptive analysis, Spearman correlation analysis and multivariate linear stepwise regression were performed. Results: Variables including marital status (single), emergency department not implementing palliative care, no palliative care training and true cooperation dimension were selected as independent predictors and explained 19.9% of variation in the regression model. Conclusions: Interventions to improve healthy work environments, offering palliative care training, advocating for policies in palliative care and offering support to unmarried nurses can advance nurses' palliative care competence. Implications for nursing management: This is the first study of emergency care nurses in China aimed at identifying predictors associated with palliative care self‐competence. It is significant in that palliative care training and a cooperative work environment are required to encourage the development of palliative care.